Development of a BODIPY-based fluorescent probe for imaging pathological tau aggregates in live cells. Issue 10 (13th January 2017) - Lim, Sungsu; Haque, Md. Mamunul; Su, Dongdong; Kim, Dohee; Lee, Jun-Seok; Chang, Young-Tae; Kim, Yun Kyung
Abstract : As a cell-permeable imaging probe, BD-tau selectively labeled pathological tau aggregates in live neuronal cells. Abstract : Neuronal accumulation of tau aggregates is a pathological hallmark in multiple neurodegenerative disorders, collectively called tauopathies. A tau aggregation sensor that can monitor abnormal tau aggregation in neurons would facilitate the study of tau aggregation processes and the discovery of tau aggregation blockers. Here, we describe a BODIPY-fluorescence sensor (BD-tau ) that selectively responds to pathological tau aggregates in live cells.